Evaluation of the heart rate and arrhythmias following the Maze procedure for chronic atrial fibrillation - Cunha,Bartira (1999)
PURPOSE: To assess the presence and the prevalence of arrhythmias and the variability of the heart rate in the medium-term postoperative period following the maze procedure for chronic atrial fibrillation (AF). METHODS: Seventeen patients with a mean age of 51.7±12.9 years, who previously underwent the maze procedure without cryoablation for chronic atrial fibrillation, were evaluated with the 24 hour electrocardiogram (ECG) - Holter monitoring from the 6th month after the operation. Valvular and coronary procedures were concomitantly performed. RESULTS: The mean heart rate during Holter monitoring was 82±8bpm; the maximal heart rate was 126 ± 23bpm and the minimal heart rate 57±7bpm. Sinus rhythm was found in 10 (59%) patients and atrial rhythm was found in 7 (41%). Supraventricular extrasystoles had a rate of 2.3±5.5% of the total number of heartbeats and occurred in 16 (94%) patients. Six (35%) patients showed nonsustained atrial tachycardia. Ventricular extrasystoles, with a rate of 0.8±0.5% of the total heartbeats, occurred in 14 (82%) patients. The chronotropic competence was normal in 9 (53%) patients and attenuated in 8 (47%). The atrioventricular conduction (AV) was unchanged in 13 (76%) patients and there were 4 (24%) cases of first degree atrioventricular block (AVB). CONCLUSION: After the maze procedure, the values for the mean heart rate, AV conduction and chronotropic competence approach the normal range, although some cases show attenuation of the chronotropic response, first degree AV block or benign arrhythmias.